Extraction of Enzymes from Four Fungi and Their Use to Improve the Nutritive Value of Groundnut Pod for Broiler Feeding - Lawal, T.E.; Iyayi, E.A.; Adeniyi, B.A.; Adaramoye, O.A. (International Journal of Poultry Science, 2010)
Enzymes were extracted from four fungi: Aspergillus niger, Trichoderma viride, Rhizopus stolonifer and Mucor mucedo. The purified enzyme extracts were used to degrade Groundnut Pod (GNP) in solid state. Undegraded GNP-, degraded GNP- and Roxazyme G2G-based diets were fed to starter and finisher broilers at the rates 70 and 100 g kg-1 of diet, respectively. There was a production of a broad spectrum of enzymes from the 4 fungi. Treatment of the GNP with the fungal enzyme extracts caused a more significant (p<0.05) reduction in the crude fibre and complex carbohydrate fractions and an increase in the crude protein, metabolizable energy and phosphorus in the GNP compared to the undegraded and Roxazyme treated GNP. The amounts of glucose, fructose, galactose and sucrose in the GNP were significantly (p<0.05) increased on biodegradation with the fungal enzyme extracts. Enzyme extracts from M. mucedo and R. stolonifer were more superior in this regard compared to extracts from the other fungi. Diets containing the degraded GNP resulted in significantly (p<0.05) reduced viscosity, better apparent nutrient digestibility and performance in broilers compared to the other diets. Results suggest the possibility of production of a multienzyme complex from some common tropical fungi. These enzyme complexes are more effective in biodegrading complex carbohydrates of by-products like GNP than Roxazyme which is specific for cereal based diets.